Aquifer lithology affects shallow groundwater quality more than nitrogen fertilizer form and placement method in an Iowa agricultural field. Issue 2 (19th May 2021) - Schilling, Keith E.; Streeter, Matthew T.; Slater, Brennan; Vogelgesang, Jason; Clair, Marty St.; Martin, Anthony
Abstract: Excessive nutrient loss threatens local and regional water resources, and many midwestern U.S. states are adopting nutrient reduction strategies to reduce export of N and P. A common practice to reduce N loss is improved fertilizer management. In this study, we used a strip trial design to assess the effects of split N application form (urea and urea ammonium nitrate [UAN]) and placement method (broadcast, coulter, Y‐drop) on corn ( Zea mays L.) yields and shallow groundwater quality at an agricultural field at Kirkwood Community College in Cedar Rapids, IA. Twelve shallow monitoring wells were installed within the production field and sampled 14 times across a corn–soybean [ Glycine max (L.) Merr.] rotation. Results showed that split application of UAN applied with either coulter injection or Y‐drop method produced approximately 8–11% higher corn yields than broadcast urea, but no statistically significant relation was found between groundwater quality and N form and placement method. Instead, we report that groundwater quality and levels were significantly influenced by variations in aquifer lithology. Groundwater within fine‐textured glacial till had significantly higher dissolved reactive P, SO4, and specific conductivity, whereas groundwater within the sand aquifer had a deeper water table and had higher NO3 –N and dissolved oxygen. Study results suggest aquifer lithology can play a much larger role than varying the N form and application method on shallow groundwater quality in agricultural fields. Core Ideas: Corn yields were higher during split application of UAN using either coulter injection or Y‐drop. There was no significant relation of groundwater quality to N form and placement method. Groundwater geochemistry varied depending on whether aquifer was sandy or fine textured.